Supplementation of Biopeptide from Chicken Feet to the Immune System and Growth of Broiler Chicken - Aulia Rizaldi Hafiz Hakim; Bambang Hartoyo; Sri Rahayu; Elly Tugiyanti; Munasik Munasik (Buletin Peternakan, 2023)
The safety of poultry products, especially broiler chickens, can be stated to be relatively low. Antibiotic growth promoter (AGP) is used to improve chicken performance and maintain immunity. The ban on the use of AGP triggers the innovation of other materials to replace the function of AGP. Biopeptide is a solution that can be used. Biopeptides can be made from materials with a high protein content, for example, waste from chicken slaughterhouses. The waste that can be used is chicken feet, biopeptides produced from hydrolytic proteins have antioxidant and antimicrobial properties. These properties can improve the performance and immune system of broiler chickens. The aim of the study was to examine the supplementation of biopeptides from chicken feet on the immune system (total Escherichia coli and internal organ) and the growth of broiler chickens. The research material was 200 day old chickens of broiler strain cobb unsex, which were reared for 42 days of the rearing period. The treatment feeds were P0: basal feed, P1 basal feed + 2% biopeptide, P2: basal feed + 4% biopeptide, P3: basal feed + 6% biopeptide. The collected data were analyzed using analysis of variance with the Tukey test (BNJ). The results showed that biopeptide supplementation from chicken feet had a significant (P<0.05) effect on total Escherichia coli, spleen weight, bursa of Fabricius weight, body weight gain, and feed efficiency for broiler chickens. However, the results of the study had no significant effect (P>0.05) on liver weight and Avian Influenza antibody titers for broiler chickens. Biopeptide supplementation from chicken feet can reduce total Escherichia coli, and spleen weight, and increase the bursa of Fabricius weight, body weight gain, and feed efficiency for broiler chickens. Biopeptide supplementation from chicken feet of 6% gave the best results in body weight gain and feed efficiency.